2008
DOI: 10.3828/tpr.79.2-3.3
|View full text |Cite
|
Sign up to set email alerts
|

Steering towards growth: Symbolic urban preservation in Beijing, 1990–2005

Abstract: This article examines the rise of symbolic urban preservation as a means of urban growth in the spatial transformation of Beijing from 1990 to 2005. The author argues that urban preservation, often considered to be in opposition to demolition and redevelopment, is nevertheless adopted by public officials and developers in Beijing as a more sophisticated instrument to achieve urban growth. While the housing renewal programme led to the demolition of a large number of courtyard houses and the construction of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Thus, planning power delegated to the city is embedded in an institutional building process, associated with new regulations and responsibilities. The impact of power decentralization on urban planning has been addressed by scholars such as Xu and Ng (1998), Wu (2007), Wu and Zhang (2008) and Zhang (2008). Although the focus of these studies varied, they have suggested that the increasing role of city (local) government in urban planning has led to a growing concern on local particulars.…”
Section: Planning and Diversity In China: From Elimination To Incorpomentioning
confidence: 98%
“…Thus, planning power delegated to the city is embedded in an institutional building process, associated with new regulations and responsibilities. The impact of power decentralization on urban planning has been addressed by scholars such as Xu and Ng (1998), Wu (2007), Wu and Zhang (2008) and Zhang (2008). Although the focus of these studies varied, they have suggested that the increasing role of city (local) government in urban planning has led to a growing concern on local particulars.…”
Section: Planning and Diversity In China: From Elimination To Incorpomentioning
confidence: 98%
“…Therefore, in spite of preservation's near dogmatic pursuit of authenticity, the results contradict the original goals and now instead seek to present the most authentic replica (Aygen 2013). Chinese historic cities have recently witnessed a significant trend in this direction (Zhang 2008). Beyond the issue of authenticity, the values associated with heritage are becoming increasingly pluralistic (Avrami, Mason, and Some of the expanding expected functions of heritage have been as a tool to address social problems or encourage development (Matero 2011;Pereira Roders and van Oers 2011).…”
Section: The Sociocultural and Anthropological Ramifications Of Heritagementioning
confidence: 99%
“…Again, the tourism operator's task is simplified if limits are placed on what can be commodified and where. Through zoning or special historic or conservation designations, state agencies reserve tourism sites from productive activities that would lessen their allure (Molotch, 1993;Zhang, 2008). Withholding land from commodification by limiting how people can use and exchange it makes it easier for managers to maintain the appearance of authenticity.…”
Section: Tourism's Peculiar Commodificationsmentioning
confidence: 99%